Sthenelais limicola - Barnich, Ruth; Haaren, Ton Van (Zenodo, 2021)
Sthenelais limicola (Ehlers, 1864) (emended) Figs 1–2 Sigalion limicola Ehlers, 1864: 120. Sthenelais leiolepis Claparède, 1868: 406–409, pl. 4 fig. 3, pl. 6 fig. 1 (description sufficient; see also Barnich & Fiege 2003). Sthenelais haddoni McIntosh, 1897a: 403. Syn. nov. Sthenelais filamentosus Ditlevsen, 1917: 50, pl. 4 fig. 6, pl. 5 fig. 9. Syn. nov. ? Aphrodita arcta Dalyell, 1853: 170, pl. 24 fig. 14 (see McIntosh 1900; however, description insufficient). Sthenelais limicola – Pruvot & Racovitza 1895: 473, pl. 20 figs 122–123. — McIntosh 1900: 417, pl. 29 fig. 3, pl. 31 fig. 6, pl. 34 figs 9–11, pl. 42 figs 1–4. — Fauvel 1923: 113, fig. 42a–g. — Chambers 1985: 29–30, figs 1b, 2a, 15b–c, 21b–e. — Hartmann-Schröder 1996: 83 fig. 28. — Chambers & Muir 1997: 158, fig. 51. — Barnich & Fiege 2003: 132, fig. 65. — Gil 2011: 947. — Núñez et al. 2015: 244, fig. 98. Diagnosis Dorsal cirri absent on segment 3. Ventral body surface smooth. Outer elytral margin with irregular extensions (anterior elytra) or notched (posterior elytra); elytral surface smooth, except for some microtubercles near anterior margin. Parapodial stylodes smooth, slender, cirriform; notopodia with few long dorsal papillae; margins of anterior neuropodial bracts smooth. Notochaetae tapering to simple capillary tip. Type material (examined) The types of Sthenelais filamentosus were available for study: ICELAND • 5 syntypes; Northeast Atlantic, S Iceland, Medelland Bugt; 19 Jul. 1903; EtOH preserved; depth 70–90 fathoms (128–165 m); NHMD 658820. The type material of the following species is probably lost or was never deposited (type localities in brackets): Sigalion limicola (Croatia, Quarnero, Adriatic Sea), Sthenelais leiolepis (Italy, Gulf of Naples, W Mediterranean Sea) and Sthenelais haddoni (off SW Ireland, Northeast Atlantic). Other material (examined) UNITED KINGDOM • 2 specs; NW Irish Sea; stn CEFNWIS04 154a; 28 Jul. 2004; EtOH preserved; TUM 37563 (Figs 1B–C, 2) • 1 spec.; Irish Sea, Liverpool Bay; stn CEFSZ07 Z02a; 19 Feb. 2008; EtOH preserved; TUM 43034 • 3 specs; S England, Hastings; stn CEFAY04 L6Ya; 30 Aug. 2004; EtOH preserved; TUM 33648. Further Mediterranean material, see Barnich & Fiege (2003). Description PROSTOMIUM. Median antenna with long, smooth, tapering style; ceratophore with large auricles. Lateral antennae fused to inner dorsal side of tentaculophores, very short, not reaching half the length of the dorsal tentacular cirri. Two pairs of eyes present (Fig. 1A). TENTACULOPHORES. Dorsal tentacular cirri shorter than median antenna, of similar shape.Ventral tentacular cirri shorter than dorsal ones (Fig. 1A). ELYTRA. Outer lateral margin with irregular extensions (anterior elytra) or notched (posterior elytra); surface smooth, except for some microtubercles near anterior margin (usually disappearing in posterior elytra) (Fig. 1B–C). CIRRI. Dorsal cirri absent from segment 3. Ventral cirri without basal knob and without long basal papillae (Fig. 2A–B). PARAPODIA. Stylodes without papillae, slender, cirriform. Parapodia of anterior body with stylodes present on anterior side of notopodial bract, on neuropodial acicular lobe and distally on upper and lower parts of large bilobed posterior bracts; number and length of distal stylodes decreasing along body. Margins of anterodorsal and anteroventral bracts smooth. Additional long, dorsal papillae on notopodia, a single papilla on anteriormost segments, up to 5 more posteriorly (Fig. 2A–B). CHAETAE. Notochaetae slender, spinous, tapering to simple capillary tip. Upper neurochaetae slender compound spinigers with multi-articled blade; slender compound falcigers with multi-articled blade and minutely bidentate tip; and few simple, spinous chaetae. Middle neurochaetae stout compound falcigers with short single- or bi-articled blade and bidentate tip. Lower neurochaetae slender compound falcigers with multi-articled blade and minutely bidentate tip (Fig. 2C–G). SIZE. Length up to 100 mm, width up to 3 mm for 200 segments (see Chambers & Muir 1997). Specimen figured, TUM 37563 (Figs 1B–C, 2): complete specimen, length 50 mm, width 1.5 mm for 128 segments. Syntypes of S. filamentosus , NHMD 658820: 5 anterior fragments ranging in length from 10 mm to 25 mm, width all about 3 mm for 23 to 52 segments. Remarks The description above is emended for the terminology used in describing the neuropodial bracts, for the presence of long, dorsal papillae on the notopodia and for the length and number of stylodes along the body: they are very long on segment 2 (some nearly reaching the length of the chaetae), becoming shorter on the following parapodia; this character led Ditlevsen (1917) to name his new species filamentosus . The syntypes of S. filamentosus are in good condition and our examination revealed that they also show the other diagnostic characters of S. limicola as described above. Sthenelais limicola (Ehlers, 1864) predates S. filamentosus Ditlevsen, 1917, which becomes its junior synonym. The type material of Sthenelais haddoni is probably lost; it consisted of a posterior fragment with completely smooth elytra presenting the typical lateral notch of S. limicola (see description in McIntosh 1897a). Sthenelais limicola has priority and S. haddoni becomes its junior synonym. Compared to other species of the genus, Sthenelais limicola presents a number of remarkable characters: The compound neurochaetae include not only falcigers, but also spinigers. The anteriormost segments of Sthenelais articulata Kinberg, 1856 also show some compound spinigers (see Pettibone 1971), but this type of chaetae was not listed as a diagnostic generic character by Pettibone or any subsequent workers. Compound spinigers in addition to falcigers are found in other sigalionid genera, for example in Eusthenelais hibernica , the type species of Eusthenelais (see below). However, this genus clearly differs by the presence of a pair of dorsal cirri on segment 3. The presence of additional long papillae dorsally on the notopodia is another remarkable character. So far, such papillae have not been described for any other species of Sthenelais . Similar papillae are found ventrally on the neuropodia of some, but not all, species of Willeysthenelais (see Pettibone 1971). All members of this genus are characterised by additional long papillae on the bases of the ventral cirri. Consequently, these remarkable characters (presence of spinigers in addition to falcigers and long dorsal papillae on notopodia) might justify the erection of a new genus. In their phylogenetic study of Aphroditiformia combining molecular and morphological data, Gonzalez et al. (2018) found that Sthenelais limicola formed a clade with Fimbriosthenelais longipinnis and Willeysthenelais diplocirrus (Grube, 1875), while Sthenelais boa formed a clade with Pholoides asperus (Johnson, 1897) and Pholoides dorsipapillatus (Marenzeller, 1893). This seems to confirm our opinion that the current generic assignment of Sigalion limicola should be reconsidered. A more detailed study combining molecular data of a larger number of Sthenelais species with the emended diagnostic characters described herein would be desirable to justify the erection of a new genus for Sigalion limicola . However, in a personal comment B. Gonzalez stated that there are currently not enough suitable specimens available to conduct a more detailed molecular study. Distribution and habitat Widely reported throughout the area. In the Northeast Atlantic present around the British Isles (RB data, based on TUM reference collection, and Chambers 1985), Northern and Central North Sea (RB and TvH data), in the Skagerrak, Kattegat and northern Öresund (Hartmann-Schröder 1996), along the French Atlantic coast (Fauvel 1923), and around the Iberian Peninsula (Núñez et al. 2015). In the Mediterranean Sea confirmed for the Western Mediterranean and the Adriatic Sea and reported from other areas (Barnich & Fiege 2003). Also recorded from the Northwest and Southeast Atlantic; however, these records require confirmation. Occurring on muddy substrates at depths of 20 to 1550 m. : Published as part of Barnich, Ruth & Haaren, Ton Van, 2021, Revision of Sthenelais Kinberg, 1856, Fimbriosthenelais Pettibone, 1971 and Eusthenelais McIntosh, 1876 (Polychaeta, Sigalionidae) in the Northeast Atlantic, pp. 138-171 in European Journal of Taxonomy 740 on pages 145-148, DOI: 10.5852/ejt.2021.740.1287, http://zenodo.org/record/4649646 : {"references": ["Ehlers E. 1864. Die Borstenwurmer (Annelida Chaetopoda) nach systematischen und anatomischen Untersuchungen. 1. Band. Wilhelm Engelmann, Leipzig. https: // doi. org / 10.5962 / bhl. title. 2081", "Claparede E. 1868. Les Annelides chetopodes du Golfe de Naples. Memoires de la Societe de Physique et d'Histoire naturelle de Geneve 19 (2): 313 - 584.", "Barnich R. & Fiege D. 2003. The Aphroditoidea (Annelida, Polychaeta) of the Mediterranean Sea. Abhandlungen der Senckenbergischen Naturforschenden Gesellschaft 559: 1 - 167.", "McIntosh W. C. 1897 a. Note on Irish annelids in the Museum of Science and Art, Dublin. No. I. Scientific Proceedings, Royal Dublin Society 8 (5): 399 - 404.", "Ditlevsen H. 1917. Annelids. The Danish Ingolf Expedition 4 (4): 1 - 71.", "Dalyell J. G. 1853. The Powers of the Creator Displayed in the Creation: or, Observations on Life Amidst the Various Forms of the Humbler Tribes of Animated Nature with Practical Comments and Illustrations. Volume 2. John van Voorst, London.", "McIntosh W. C. 1900. Polychaeta. Amphinomidae to Sigalionidae. A Monograph of the British Annelids 1 (2): 215 - 444.", "Pruvot G. & Racovitza E. G. 1895. Materiaux pour la faune des Annelides de Banyuls. Archives de Zoologie experimentale et generale, serie 3 3: 339 - 492.", "Fauvel P. 1923. Polychetes errantes. Faune de France 5: 1 - 488.", "Chambers S. J. 1985. Polychaetes from Scottish waters. Part 2. Families Aphroditidae, Sigalionidae, and Polyodontidae. Royal Scottish Museum Studies: 1 - 38.", "Hartmann-Schroder G. 1996. Annelida, Borstenwurmer, Polychaeta [Annelida, bristleworms, Polychaeta]. 2 nd revised Ed. The fauna of Germany and adjacent seas with their characteristics and ecology 58. Gustav Fischer, Jena, Germany.", "Chambers S. J. & Muir A. I. 1997. Polychaetes: British Chrysopetaloidea, Pisionoidea and Aphroditoidea. Synopses of the British Fauna 54: 1 - 202.", "Gil J. C. 2011. The European Fauna of Annelida Polychaeta. Vol. 2. PhD Thesis. University of Lisbon, Portugal.", "Nunez J., Barnich R., Brito M. del C. & Fiege D. 2015. Familia Sigalionidae Kinberg, 1855. In: Ramos et al. (eds) Annelida Polychaeta IV. In: Parapar J., Moreira J., Nunez J., Barnich R., Brito M. del C., Fiege D., Capaccioni-Azzati R. & El-Haddad M. Fauna Iberica 41: 216 - 251. Museo Nacional de Ciencias Naturales, CSIC, Madrid.", "Kinberg J. G. H. 1856. Nya slagten och arter af Annelider. Ofversigt af Kongliga Vetenskaps-Akademiens Forhhandlingar Stockholm 12 (9 - 10): 381 - 388 [read 1855; printed 1856].", "Pettibone M. H. 1971. Partial revision of the genus Sthenelais Kinberg (Polychaeta: Sigalionidae) with diagnoses of two new genera. Smithsonian Contributions to Zoology 109: 1 - 40. https: // doi. org / 10.5479 / si. 00810282.109", "Gonzalez B. C., Martinez A., Borda E., Iliffe T. M., Eibye-Jacobsen D. & Worsaae K. 2018. Phylogeny and systematics of Aphroditiformia. Cladistics 34 (3): 225 - 259. https: // doi. org / 10.1111 / cla. 12202"]}